Historical dictionary of kant and kantianism. - MUDROCH, VILEM (ROWMAN & LITTLEFIELD, 2020)
Immanuel Kant was one of the most significant philosophers of the modern age. Historical Dictionary of Kant and Kantianism, Second Edition contains a chronology, an introduction, appendixes, and an extensive bibliography. The dictionary section has over 500 cross-referenced entries on key terms of Kant's philosophy, Kant's major works and cover his most important predecessors and successors, concentrating especially on the relation of these thinkers to Kant himself. This book is an excellent resource for students, researchers, and anyone wanting to know more about Immanuel Kant.